Empirical Study and Comprehensive Analysis of Customer Satisfaction Regarding Online Shopping Experience Quality - Sarwo Eddy Wibowo; Sylvia Kartika Dhamayanti; Obing Zaid Sobir; Dipa Teruna Awaludin; Ahmad Syauqi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to analyze the impact of online shopping experience quality on customer satisfaction among e-commerce users. Data was obtained from 200 respondents through a five-point Likert scale questionnaire and interviews to enrich the explanation of the quantitative results. The instrument was developed through focus group discussions and validated by academics and e-commerce practitioners. The analysis was conducted using SPSS, including validity, reliability tests, and both simple and multiple linear regression. The results indicate that the quality of the online shopping experience significantly affects customer satisfaction, with a coefficient of determination of 0.63. Delivery speed and accuracy emerged as the most dominant factors (β = 0.56; p < 0.001), followed by customer service quality (β = 0.49; p < 0.01), website ease of use (β = 0.42; p < 0.01), and transaction security and payment methods (β = 0.32; p < 0.05). A total of 73% of respondents were satisfied to highly satisfied, with an average score of 4.2 on a 1-5 scale. The findings suggest that logistics performance, customer service responsiveness, interface design, and payment security are the primary factors contributing to customer satisfaction on e-commerce platforms.